Structure of Zn x Fe3− x O4 nanoparticles studied by neutron diffraction and its relation with their response in magnetic hyperthermia experiments - Lohr, Javier Hernán (2024)
The mixed zinc-ferrite spinel magnetic nanoparticles (MNPs) with the general formula ZnxFe3−xO4 are among the most extensively studied families of Fe oxides due to their interesting and diverse chemical, electronic, and magnetic properties. These systems offer the possibility of surface functionalization and possess high biocompatibility, making them highly attractive for applications in biomedicine, such as magnetic fluid hyperthermia (MFH). The efficiency of the MFH process relies on the magnetic, structural and morphological properties of the MNPs. The substitution with the Zn ion and the cationic distribution, as well as the synthesis process employed, have a direct impact on the final properties of these oxides. Therefore, it is essential to have tools that enable a comprehensive characterization of the system to assess its performance in MFH. In this study, we have synthesized four ZnxFe3−xO4 MNP systems using three different methods: two by thermal decomposition at high temperatures, one by co-precipitation, and another by co-precipitation followed by ball milling. We analyze the effect of these various synthesis processes on the magnetic and crystallographic properties, aiming to correlate them with the response of each system in MFH. Neutron diffraction data are employed to determine the cation site occupation and to investigate the correlation with the synthesis method. MFH measurements were conducted in media of diverse viscosities, revealing different values of specific loss power, thus demonstrating a clear dependence on the synthesis process and Zn content.